2018
DOI: 10.1017/s0016756818000304
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry, age and origin of the Mons Claudianus TTG batholith (Egypt): insight into the role of Pan-African magmatism in uniting plates of Gondwana

Abstract: The tonalite–trondhjemite–granodiorite (TTG) Mons Claudianus Batholith (MCB) of Egypt is subsolvus, metaluminous to mildly peraluminous, exhibits wide ranges of SiO2, Al2O3, Sr, Rb, Zr, shows large Ba enrichment, is moderately enriched in rare earth elements (REE) and is depleted in K, Ti, Nb, Y, Hf and heavy REE (HREE), reflecting strong arc geochemical signatures. Moderate fractionation of REE and lack of Eu anomaly characterize the MCB. It is typical of high-Al TTGs of volcanic-arc affinities. U–Pb–zircon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…One Claudianus shaft (already mentionned in [18]) was also positively confirmed in the Lyon Theater using this technique. Reference values from Corsica and Claudianus were obtained from our sampling on Cavallo island, and [11,12,16]. In Pisa we studied using pXRF three shafts presumed from Corsica, Mons Claudianus and Mysia (?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One Claudianus shaft (already mentionned in [18]) was also positively confirmed in the Lyon Theater using this technique. Reference values from Corsica and Claudianus were obtained from our sampling on Cavallo island, and [11,12,16]. In Pisa we studied using pXRF three shafts presumed from Corsica, Mons Claudianus and Mysia (?…”
Section: Resultsmentioning
confidence: 99%
“…pXRF data on shafts, in particular Rb values, are often lower than reference or geological sample data, but the separation between Claudianus and Corsica fields is large enough to overcome this bias. [8,11,12,16,17], in pink, blue, green and orange ellipses, respectively. Our average pXRF data with s.d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to their relative scarcity worldwide, much lesser studies on Neoproterozoic TTGs are available. In the case of the Arabian–Nubian Shield (ANS), only a few studies on TTGs have been reported in the literature (e.g., Abdel‐Rahman, 2019, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations of other magmatic complexes within the northern part of the ANS have been carried out (e.g. Bentor, 1985;Abdel-Rahman & Doig, 1987;Abdel-Rahman & Martin, 1987;Abdel-Rahman, 1990, 1995, 2010, 2016, 2019El-Shazly & El-Sayed, 2000;Loizenbauer et al 2001;El-Sayed et al 2004;Eliwa et al 2006;Abdel-Rahman et al 2009;Bea et al 2009;Be'eri-Shlevin et al 2009, 2011Johnson et al 2011;Maurice et al 2012;Fritz et al 2013;Jarrar et al 2013;Eyal et al 2014Eyal et al , 2019Robinson et al 2014;Elisha et al 2017Elisha et al , 2019.…”
Section: Introductionmentioning
confidence: 99%